The contribution of Ibn Ishaq al-Kindi to light, optics and cryptology - Saleem, Azizullah; Othman, Raihan (IIUM Press, 2011)
The objective of this chapter is to discuss Al Kindi's contributions in the field of engineering including the theory of light, optics and cryptology. The research framework is Al Kindi's contributions to light including act of seeing, motion of rectilinear property of light, visual rays and perception